(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
Environmental planning is one of the most important plans and strategies for preserving the environment and achieving sustainable development at the level of the national economy, and with the increasing international interest in the components of the ecosystem in the planning process, mainly, and with the increasing problems and negative effects it faced represented by pollution, gas emissions, climate changes, depletion of natural resources and damage to generations present and future This called for finding a future vision, policies, plans and strategies to protect the environment. In this context, Iraq tried to devote the importance of integrating the environmental dimension with the economic and social dimension by adopting the environmental planning method that focuses in its general sense on preserving the environment and on the biological balance in order to achieve human well-being, which is the goal and purpose of development. The problem of the research is that Iraq was exposed, especially after 2003, to conflicts and wars that had significant effects on the deterioration of the Iraqi environment. Treatments of war remnants in an analytical manner within the general framework of economic plans, and one of the most important results that were reached despite the development of economic plans in the field of environment are policies and strategies that work to protect the environment, but from a practical point of view it was difficult to materialize the goals and achieve the goals under the circumstances that Iraq passed.